In vitro seed germination and seedling development of Rio Grande cherry (Eugenia involucrata DC.) - Marcelo Almeida de Oliveira Junior; Bruna do Amaral Brogio Colli; Liliane Cristina Libório Stipp; Rodrigo Rocha Latado; Sônia Maria de Stefano Piedade; Francisco de Assis Alves Mourao Filho (Ornamental Horticulture)
Trees play an important role in urban landscapes by offering ecological and functional benefits such as heat mitigation and biodiversity support. Native fruit trees, such as the Rio Grande cherry (Eugenia involucrata DC.), may have great potential to be used in this context, by providing food for local fauna and promoting ecological balance, and easily adapt to this environment. On the other hand, propagation is limited by its annual fruiting cycle, recalcitrant seeds, and the low efficiency of clonal propagation methods. Tissue culture offers a promising alternative for large-scale seedling production using in vitro germinated seedlings for micropropagation. This study aimed to optimize in vitro establishment of Rio Grande cherry by evaluating seed preparation and cultivation conditions to enhance in vitro germination and nursery tree production. Factors such as light conditions, tegument removal, MS salt concentrations, sucrose concentrations, and seed fractioning were evaluated in several distinct experiments. High germination and seedling development rates were achieved by removing the tegument and cultivating seeds in the dark. Using a complete MS medium and supplementation of 15 g L -1 of sucrose also enhanced seedling development. Despite fractioned seeds having some germination potential, seedling development was negatively affected.